The Sesbania Root Symbionts Sinorhizobium saheli and S. teranga bv. sesbaniae Can Form Stem Nodules on Sesbania rostrata, although They Are Less Adapted to Stem Nodulation than Azorhizobium caulinodans - Boivin, C. (1997)
Sesbania species can establish symbiotic interactions with rhizobia from two taxonomically distant genera, including the Sesbania rostrata stem-nodulating Azorhizobium sp. and Azorhizobium caulinodans and the newly described Sinorhizobium saheli and Sinorhizobium teranga bv. sesbaniae, isolated from the roots of various Sesbania species. A collection of strains from both groups were analyzed for their symbiotic properties with different Sesbania species. S. saheli and S. teranga bv. sesbaniae strains were found to effectively stem nodulate Sesbania rostrata, showing that stem nodulation is not restricted to Azorhizobium. Sinorhizobia and azorhizobia, however, exhibited clear differences in other aspects of symbiosis. Unlike Azorhizobium, S. teranga bv. sesbaniae and S. saheli did not induce effective stem nodules on plants previously inoculated on the roots, although stem nodulation was arrested at different stages. For Sesbania rostrata root nodulation, Sinorhizobium appeared more sensitive than Azorhizobium to the presence of combined nitrogen. S. saheli and S. teranga bv. sesbaniae were effective symbionts with all Sesbania species tested, while Azorhizobium strains fixed nitrogen only in symbiosis with Sesbania rostrata. In a simple screening test, S. saheli and S. teranga bv. sesbaniae were incapable of asymbiotic nitrogenase activity. Thus, Azorhizobium can easily be distinguished from Sinorhizobium among Sesbania symbionts on the basis of symbiotic and free-living nitrogen fixation. The ability of Azorhizobium to overcome the systemic plant control appears to be a stem adaptation function. This last property, together with its host-specific symbiotic nitrogen fixation, makes Azorhizobium highly specialized for stem nodulation of the aquatic legume Sesbania rostrata.